Postoperative Radiologic Changes in Early Recurrent Lumbar Foraminal Stenosis After Transforaminal Endoscopic Lumbar Foraminotomy for Lower Lumbar Segments - Chi-Ho Kim; Pius Kim; Chang-Il Ju; Jong-Hun Seo (Diagnostics)
Background/Objectives: One of the surgical treatments for lumbar foraminal stenosis, full endoscopic foraminotomy, is known for its numerous advantages and favourable clinical outcomes. While previous studies have analyzed preoperative radiological risk factors associated with recurrence within one year after endoscopic foraminal decompression, no research has investigated postoperative radiological changes. The aim of this study is to analyze the radiological changes occurring in cases of early recurrence within six months after endoscopic foraminal decompression. Methods: A retrospective review was conducted on patients with unilateral lumbar foraminal stenosis who underwent full endoscopic foraminotomy at a single institution. The study included 11 recurrent patients who initially experienced symptomatic improvement and sufficient neural decompression on radiological evaluation, but exhibited recurrent radicular pain and radiological restenosis within six months postoperatively. Additionally, 33 control patients with favourable clinical outcomes and no evidence of restenosis were analyzed. Preoperative and postoperative plain X-ray imaging was used to evaluate sagittal and coronal parameters reflecting spinal anatomical characteristics, including disc height, foraminal height, disc wedging, coronal Cobb’s angle, total lumbar lordosis angle, segmental lumbar lordosis angle, and dynamic segmental lumbar lordosis angle. The study aimed to analyze postoperative changes in these parameters between the recurrent and control groups. Clinical outcomes were assessed using the Visual Analog Scale (VAS). Results: There were no significant differences between the groups in terms of age, sex distribution, presence of adjacent segment disease, or existence of Grade 1 spondylolisthesis. Analysis of preoperative and postoperative radiological changes revealed that, in the recurrent group, disc height and foraminal height showed a significant decrease postoperatively, while disc wedging and the coronal Cobb’s angle demonstrated a significant increase. In contrast, the control group exhibited a significant postoperative increase in the total lumbar lordosis angle and segmental lumbar lordosis angle. Conclusions: Progressive worsening of disc wedging and the coronal Cobb’s angle, and reductions in disc and foraminal height, along with minimal improvement in lumbar lordosis following TELF, suggest the presence of irreversible preoperative degenerative changes. Careful radiologic assessment and close postoperative monitoring are essential to identify patients at risk of early recurrence.